History in uniform military ideology and the construction of Indonesia's past - McGregor, Katharine E (Asian Studies Association of Australia, 2007)
History in Uniform is the first detailed analysis of the Indonesian military's image-making efforts, and one of a very small group of studies to examine a key institution within the Indonesian military--the Armed Forces History Centre. Based on a unique set of sources that includes interviews with staff of the Centre, museum records, guidebooks, collections of military doctrine, seminar proceedings, films, textbooks, and commemorative histories of the military and the Centre, the book offers a rare examination of the significance of history to a politicized military force and to a modernizing nation